Profil Pasien Peritonitis Primer, Peritonitis Sekunder, dan Peritonitis Tersier di RSUP Prof. Dr. R. D. Kandou Tahun 2022 - Angelica M. J. Wagiu; Fadilah N. A. Kasim; Andiressanto C. Lengkong (Universitas Sam Ratulangi, 2024)
Abstract: The complex structure of abdomen makes the diagnosis and treatment of intraperitoneal infections a challenge in the practice of medicine. This study aimed to obtain the profile of primary peritonitis, secondary peritonitis, and tertiary peritonit patients treated at Prof. Dr. R. D. Kandou Hospital, Manado. This was a retrospective and descriptive study using medical records of peritonitis patients during the period January–December 2022. The results showed that most peritonitis patients treated at Prof. Dr. R. D. Kandou were males in the age group of 19-59 years. The most common peritonitis was secondary peritonitis (52 patients), followed by tertiary peritonitis (11 patients) and primary peritonitis (9 patients). Based on the etiology, hepatic cirrhosis (45%) was the most common etiology of primary peritonitis; gastric perforation (38%) was the most common etiology of secondary peritonitis; and post appendectomy (18%), post nephrostomy (18%) and leakage of sigmoid anastomosis (18%) were the most common etiologies of tertiary peritonitis. Generally patients had radiological features of preperitoneal fat depletion (44%), and subdiaphragm free air (20%). Most patients received operative treatment, and admitted to the hospital with sepsis. In conclusion, the majority of peritonitis patients suffer from secondary peritonitis, males of age group 19-59 years, with varied etiologies for each type of peritonitis. Keywords: patient profile; primary peritonitis; secondary peritonitis; tertiary peritonitis. Abstrak: Struktur abdomen yang kompleks membuat diagnosis dan pengobatan infeksi intraperitoneal menjadi tantangan dalam praktik kedokteran. Penelitian ini bertujuan untuk mengetahui profil pasien peritonitis primer, peritonitis sekunder, dan peritonitis tersier yang dirawat di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif retrospektif dengan menggunakan data rekam medis pasien peritonitis selama periode Januari – Desember 2022. Hasil penelitian mendapatkan 72 pasien peritonitis dirawat di RSUP Prof. Dr. R. D. Kandou Manado sebagai subjek penelitian. Peritonitis paling sering terjadi pada laki-laki, kelompok usia 19-59 tahun. Peritonitis yang tersering ialah peritonitis sekunder (52 pasien), diikuti peritonitis tersier (11 pasien) dan peritonitis primer (9 pasien). Berdasarkan etiologi, sirosis hati (45%) merupakan etiologi tersering peritonitis primer; perforasi gaster (38%) merupakan etiologi tersering peritonitis sekunder; serta pasca apendektomi, pasca nefrostomi dan leakage anastomosis sigmoid merupakan etiologi tersering peritonitis tersier (masing-masing 18%). Umumnya pasien memiliki gambaran radiologi penipisan lemak preperitoneal (44%), dan udara bebas subdiafragma (20%). Pasien terbanyak menerima tatalaksana operatif, dan datang dengan sepsis. Simpulan penelitian ini ialah mayoritas pasien dengan peritonitis berjenis kelamin laki-laki, kelompok usia 19-59 tahun, kategori peritonitis sekunder, dengan etiologi bervariasi untuk setiap jenis peritonitis. Kata kunci: profil pasien; peritonitis primer; peritonitis sekunder; peritonitis tersier